Changes in ponderal index and body mass index across childhood and their associations with fat mass and cardiovascular risk factors at age 15. - Laura D Howe; Kate Tilling; Li Benfield; Jennifer Logue; Naveed Sattar; Andy R Ness; George Davey Smith; Debbie A Lawlor (PLoS ONE)
Background Little is known about whether associations between childhood adiposity and later adverse cardiovascular health outcomes are driven by tracking of overweight from childhood to adulthood and/or by vascular and metabolic changes from childhood overweight that persist into adulthood. Our objective is to characterise associations between trajectories of adiposity across childhood and a wide range of cardiovascular risk factors measured in adolescence, and explore the extent to which these are mediated by fat mass at age 15. Methods and findings Using data from the Avon Longitudinal Study of Parents and Children, we estimated individual trajectories of ponderal index (PI) from 0-2 years and BMI from 2-10 years using random-effects linear spline models (N = 4601). We explored associations between PI/BMI trajectories and DXA-determined total-body fat-mass and cardiovascular risk factors at 15 years (systolic and diastolic blood pressure, fasting LDL- and HDL-cholesterol, triglycerides, C-reactive protein, glucose, insulin) with and without adjustment for confounders. Changes in PI/BMI during all periods of infancy and childhood were associated with greater DXA-determined fat-mass at age 15. BMI changes in childhood, but not PI changes from 0-2 years, were associated with most cardiovascular risk factors in adolescence; associations tended to be strongest for BMI changes in later childhood (ages 8.5-10), and were largely mediated by fat mass at age 15. Conclusion Changes in PI/BMI from 0-10 years were associated with greater fat-mass at age 15. Greater increases in BMI from age 8.5-10 years are most strongly associated with cardiovascular risk factors at age 15, with much of these associations mediated by fat-mass at this age. We found little evidence supporting previous reports that rapid PI changes in infancy are associated with future cardiovascular risk. This study suggests that associations between early overweight and subsequent adverse cardiovascular health are largely due to overweight children tending to remain overweight.